2022
DOI: 10.5294/laclil.2022.15.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Needs and Professional Development: A Systematic Review

Abstract: This study utilizes a systematic review process to synthesize research on content and language integrated learning (CLIL) teachers’ self-reported needs and professional development. In order to draw connections between these two areas of research and highlight gaps, this study adopted a framework composed of seven competences: linguistic, pedagogical, scientific knowledge, organizational, interpersonal, collaborative, and reflective. Six electronic databases were used, and a forward and backward search was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
(47 reference statements)
1
5
0
Order By: Relevance
“…collaboration, see Kim and Graham, 2022;Pérez Cañado, 2018). However, the existing literature does not yet provide sufficient insight into which aspects of TPD may have an effect on student learning outcomes in the particular context of ILS&T instruction.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…collaboration, see Kim and Graham, 2022;Pérez Cañado, 2018). However, the existing literature does not yet provide sufficient insight into which aspects of TPD may have an effect on student learning outcomes in the particular context of ILS&T instruction.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Improving the professional development of teachers is normally understood as positively influencing students' learning (Kim and Graham 2022). Thinking about how to enhance training programmes for both in-and pre-service teachers is a key element for achieving teaching and learning process success.…”
Section: Professional Development In Clil: Integrating Video-based Te...mentioning
confidence: 99%
“…Despite the fact that the study of the professional development of CLIL teachers has been increasing in recent times (Kim and Graham 2022), few studies have explored how video technology benefits teacher's professional development, to the best of the author's knowledge. According to Lo (2020), scarce research is found related to CLIL professional development programmes, including studies that integrate the use of videobased programmes to enhance professional development.…”
Section: Introductionmentioning
confidence: 99%
“…These realities are highly influential in shaping teachers' beliefs and practices and, thus, they have a relevant role in meeting the desired educational goals and outcomes (Lumpe et al, 2000). Ford (1992) (Banegas, 2020;Barrios & Milla-Lara, 2020;Kim & Graham, 2022;Lancaster, 2018;Lazarevic, 2022;Marsh, et al, 2012;Meyer, 2010;Pérez-Cañado, 2017Pistorio, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research has long advocated for specifically designed programmes that provide practitioners with good theoretical and methodological knowledge and help them acquire expertise (Azparren-Legarre, 2020Banegas, 2012;Breeze & Azparren-Legarre, 2021;Bueno-Alastuey & Villarreal, 2021;Hillyard, 2011;Kim & Graham, 2022;Marsh et al, 2012;McDougald, 2015;Mehisto & Asser, 2007;Pérez-Cañado, 2016a, 2016bPistorio, 2009). However, there seems to be no such provision as a general lack of teacher training has been reported (Cabezas-Cabello, 2010;Lancaster, 2016Lancaster, , 2018Lasagabaster & Ruiz de Zarobe, 2010;Pérez-Cañado, 2016b, and countries seem to be generally failing at preparing their teachers (Mehisto et al, 2008;Pineda et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%